Influence of Chemical Etching on Surface Micro-Geometry of Titanium Implants - Martikan, Anton; Struharnansky, Jozef; Stancekova, Dana; Czan, Andrej; Hatala, Michal (Manufacturing Technology Journal, 2015)
The article deals with influence of chemical etching and polishing on some roughness parameters of titanium parts surface, designed for implantation into human organism. Titanium alloy Ti-6Al-4V was used for the experiment. Analysed samples were created by conventional mechanical machining methods as milling, grinding and polishing. Influence on surface and quantity of removed material by acid solution was analysed. Three methods of sample surface finishing were used, each resulting in variety of surface quality, and then two methods of chemical polishing, differed by reaction time of acid with samples surface. The samples surface was analysed optically, using stereo-microscope and evaluated roughness parameters as arithmetic average roughness Ra, ten-point mean roughness Rz, profile skewness Rsk and kurtosis Rku were measured. The modification of these parameters after the reaction was measured and analysed.
Keywords: titanium alloys; implants; chemical polishing; surface micro-geometry